Optimization of Growth Conditions of Desulfovibrio desulfuricans Strain REO-01 and Evaluation of Its Cd(II) Bioremediation Potential for Detoxification of Rare Earth Tailings - Ping Zhang; Chaoyang Wei; Fen Yang (Microorganisms)
To promote environmentally sustainable remediation and resource recovery from ion-adsorption rare earth tailings (IRET), this study comprehensively investigated the previously isolated strain REO-01 by examining its sulfate-reducing performance, Cd(II) immobilization potential, and physiological and biochemical responses under varying environmental conditions. Strain REO-01 was identified as a Gram-negative facultative anaerobe with strong sulfate-reducing activity and effective Cd(II) immobilization capacity. During a 96 h incubation period, the strain entered the exponential growth phase within 36 h, after which the OD600 values plateaued. Concurrently, the culture pH increased from 6.83 to 7.5, and the oxidation-reduction potential (ORP) declined to approximately −300 mV. Cd(II) concentrations decreased from 0.2 mM to 3.33 μM, corresponding to a removal efficiency exceeding 95%, while sulfate concentrations declined from 1500 mg/L to 640 mg/L, with a maximum reduction efficiency of 66.16%. The strain showed optimal growth at 25–40 °C and near-neutral pH (6–7), whereas elevated Cd(II) concentrations (≥0.2 mM) significantly inhibited cell growth. A sulfate concentration of 1500 mg/L was found to be optimal for cellular activity. Among the tested carbon sources, sodium lactate at 4.67 g/L yielded the most favorable results, reducing ORP to −325 mV, increasing pH to 7.6, and lowering Cd(II) and sulfate concentrations to 3.33 μM and 510 mg/L, respectively. These findings highlight the strong potential of strain REO-01 for simultaneous sulfate reduction and Cd(II) remediation, supporting its application in the in situ bioremediation and resource utilization of rare earth tailings.